Clinical Outcome and Glenoid Morphology After Arthroscopic Repair of Chronic Osseous Bankart Lesions: A Five to Eight-Year Follow-up Study. (18th November 2015) - Kitayama, Soichiro; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Kawai, Nobuaki; Tokai, Morihito; Ohnishi, Kazutomo; Ueda, Yusuke; Hoshika, Shota; Kitamura, Nobuto; Yasuda, Kazunori; Moriishi, Joji
Abstract : Background: Arthroscopic osseous Bankart repair for shoulders with chronic recurrent anterior instability has been reported as an effective procedure with promising short-term outcomes. However, to date, we know of no report describing longer-term outcomes and glenoid morphologic change. The purpose of the present study was to report intermediate to long-term outcomes and glenoid morphologic change after arthroscopic osseous Bankart repair in patients with substantial glenoid bone loss. Methods: A consecutive series of eighty-five patients with traumatic anterior glenohumeral instability associated with a chronic osseous Bankart lesion underwent arthroscopic repair from January 2005 through December 2006. Forty-six patients with bone loss of >15% of the inferior glenoid diameter relative to the assumed inferior circle regardless of the fragment size were selected as candidates for this study. Thirty-eight patients (83%), including thirty-four male and four female patients, with a mean age of 23.4 years (range, fifteen to thirty-six years) at the time of surgery, were available for final follow-up at a mean of 6.2 years (range, 5.0 to 8.1 years) after surgery. Results: One patient had a redislocation during a traffic accident five months after surgery before obtaining an osseous union. The mean Rowe score and the mean Western Ontario Shoulder Instability Index improved significantly from 30.7 points preoperatively to 95.4 points postoperatively and from 26.5% to 81.5%, respectively. Although the mean preoperative fragment size was measured as only 4.7%, the mean glenoid bone loss improved from 20.4% preoperatively to −1.1% postoperatively. Conclusions: Arthroscopic osseous Bankart repair is an effective primary treatment for shoulders with substantial glenoid bone loss as it provides successful outcomes without recurrence of instability once osseous union is obtained. Glenoid morphology can be normalized during the intermediate to long-term postoperative period, even in shoulders with a smaller fragment. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.